Performance analysis and optimisation for edge connection of JSCC system based on double protograph LDPC codes - Hong, Shaohua; Chen, Qiwang; Wang, Lin (IET communications, 2018)
For a joint source–channel coding system based on double protograph low-density parity-check codes, the exchange of extrinsic information through edge connection between the source code and channel code is essential for good performance. In this study, the relationship between the performance and edge connection in the tanner graph is analysed and it has never been seen in the literature to the authors' knowledge. Both the joint protograph extrinsic information transfer and simulation results indicate that the edge connection should be optimised in practical applications since it plays an important role in the bit error rate performance and an optimisation scheme for the edge connection is put forward to enhance performance.